Building capacity of healthcare professionals and community members to address climate and health threats in The Bahamas: Analysis of a green climate fund pilot workshop - William Hamilton; Calae Philippe; James Hospedales; Caleb Dresser; Bridgette Colebrooke; Nicola Hamacher; Kimberly Humphrey; Cecilia Sorensen (Elsevier, 2023)
Climate change is a preeminent threat to health and health systems in The Bahamas. Climate and health resilience depends upon a knowledgeable and coordinated healthcare system and workforce that is highly connected and coordinated with a knowledgeable and empowered community. We present the methodology and results of a novel educational workshop, designed to increase the knowledge and awareness of health care professionals and community members with the goal of empowering them to engage in climate mitigation and adaptation strategies. Following the training, participants demonstrated increased knowledge of the causes of climate change, health exposures, climate-sensitive diseases, and vulnerable populations relevant to The Bahamas. Further, participants reported high levels of willingness and readiness to tackle climate change and its health consequences. Results from this workshop suggest that such a model may serve as a guide for building grass-roots resilience in communities worldwide.